Surface chemistry of the titanium powder studied by XPS using internal standard reference. (1st January 2017) - Shvab, Ruslan; Hryha, Eduard; Nyborg, Lars
ABSTRACT: Surface chemistry of the titanium powder has particularly growing interest due to the increasing application of titanium components prepared by powder metallurgy, in particular metal injection moulding and additive manufacturing. Due to the high chemical activity, number of titanium oxides, calcium and complex Ca–Ti–oxides can be expected on the component/medical implant surface, depending on powder and component manufacturing and post-treatment, but are very difficult to analyse due to the lack of the experimental data and analysis methodology. Therefore, a methodology for the analysis of the surface chemistry of the Ti-powder by XPS utilising internal standard reference was developed. The obtained methodology was used for the surface analysis of titanium powder and identification of its surface oxide composition. The results show that the powder surface is covered by TiO2 layer in the form of rutile with a thickness of 4.4 nm. Carbon and nitrogen impurities were also found present on the powder surface. GRAPHICAL ABSTRACT: